Natural cycle increases the live-birth rate compared with hormone replacement treatment for frozen-thawed single euploid blastocyst transfer - Li, Xiaofang; Gao, Yan’e; Shi, Juanzi; Shi, Wenhao; Bai, Haiyan (Frontiers in Endocrinology, 2022)
Background A number of studies have compared the clinical outcomes between the two endometrial preparation methods: natural cycles (NCs) and hormone replacement treatment (HRT) before frozen embryo transfer, but the results were conflicting. In order to mitigate the potential effect of embryos per se, several researchers have worked on this subject for euploid blastocyst transfer, but the results were still inconsistent. Therefore, the present study was aimed to investigate the clinical outcomes between HRT and NC for autologous single vitrified–warmed euploid blastocyst transfer based on our data. Methods A total of 598 frozen-thawed single euploid blastocyst transfer cycles in the assisted reproductive center of Northwest Women’s and Children’s Hospital from January 2014 to May 2021 were retrospectively analyzed. Women were stratified into the NC (n = 125) or HRT (n = 473) group according to the patient’s preference and the physician’s guidance. Multivariate regression models and subgroup analysis were constructed to analyze the association between endometrial preparation and live birth. Results Women in the NC group had a higher live birth rate (68.80% versus 58.35%, P = 0.034) and a lower risk of total pregnancy loss (8.51% versus 21.14%, P = 0.005) when compared with women in the HRT group. The biochemical pregnancy rate (75.20% versus 74.00%, P = 0.784) and clinical pregnancy rate (74.40% versus 69.98%, P = 0.334) were similar between the two groups (NC versus HRT). NC was associated with an increased odds of live birth compared with HRT by different multivariable analysis models (Model 1: adjusted odds ratio [aOR], 95% confidence interval [CI]: 0.57, 0.36 - 0.90; Model 2: aOR, 95%CI: 0.57, 0.35 - 0.92). In addition, the increased chance of live birth in the NC group was found in all subgroups. No major obstetrical complications and two malformation livebirths were reported. Conclusions In women undergoing single euploid frozen blastocyst transfers, the NC group was associated with a lower pregnancy loss rate and an ultimately higher live birth rate than the HRT group. Although HRT is convenient for both clinicians and patients, the lower live birth rate should be taken into account and NC might be the first choice of endometrial preparation method.